2010
DOI: 10.1183/09059180.00006009
|View full text |Cite
|
Sign up to set email alerts
|

Heliox, dyspnoea and exercise in COPD

Abstract: One of the most important determinants of physical and mental well-being of people with chronic obstructive pulmonary disease (COPD) is participation in physical activity. The ability to alter the sensation of dyspnoea during exercise may improve both exercise duration and intensity. Despite the low density, inert nature, strong safety profile and multiple applications of helium gas, the potential benefit of helium-oxygen gas mixtures as an adjunct therapy to modify disease symptoms and exercise capabilities i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
23
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 31 publications
0
23
0
3
Order By: Relevance
“…Importantly, as for the results of their review analysis, HUNT et al [6] concluded that: ''Overall, the eight studies included in this review presented a case for high level, low risk of bias evidence to support the effectiveness of heliox in improving the intensity and endurance of exercise when compared to room air for people with COPD.''. In contrast, the review by HUNT et al [6] failed to demonstrate a significant reduction in exertional dyspnoea induced by heliox breathing. It should be noted, however, that dyspnoea was not the primary outcome in these studies and that differences in the studied patient population and exercise protocols utilised (i.e.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Importantly, as for the results of their review analysis, HUNT et al [6] concluded that: ''Overall, the eight studies included in this review presented a case for high level, low risk of bias evidence to support the effectiveness of heliox in improving the intensity and endurance of exercise when compared to room air for people with COPD.''. In contrast, the review by HUNT et al [6] failed to demonstrate a significant reduction in exertional dyspnoea induced by heliox breathing. It should be noted, however, that dyspnoea was not the primary outcome in these studies and that differences in the studied patient population and exercise protocols utilised (i.e.…”
mentioning
confidence: 99%
“…In their study, HUNT et al [6] clearly illustrate the rationale beyond the use of heliox during exercise in COPD and adequately summarise the relevant results of these research articles. Importantly, as for the results of their review analysis, HUNT et al [6] concluded that: ''Overall, the eight studies included in this review presented a case for high level, low risk of bias evidence to support the effectiveness of heliox in improving the intensity and endurance of exercise when compared to room air for people with COPD.''. In contrast, the review by HUNT et al [6] failed to demonstrate a significant reduction in exertional dyspnoea induced by heliox breathing.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Alongside this presentation of the advances made in COPD therapies, the difficulty in treating patients and designing trials for such a heterogeneous disease was discussed, and the need for not only the publication of treatment guidelines, but a more universal adherence to them, was emphasised. Also featured in the March 2010 issue was a systematic review of the effects of Heliox therapy on exercise performance and dyspnoea perception in COPD patients [15], as well as a discussion of the mechanisms by which pulmonary rehabilitation can benefit those with COPD, and how this benefit may extend to a wider population in the future [16]. Important advances in the understanding of the diffuse parenchymal lung diseases were communicated by HARARI and CAMINATI [17] in June 2010, with particular interest in the progress made in the field of idiopathic pulmonary fibrosis.…”
mentioning
confidence: 99%